A cytomorphometric analysis of pulmonary and mediastinal granulomas: Differentiating histoplasmosis from sarcoidosis by fine‐needle aspiration. Issue 1 (15th October 2014) - Gailey, Michael P.; Keeney, Matthew E.; Jensen, Chris S.
<x xml:space="preserve">Abstract</x> BACKGROUND Histoplasmosis and sarcoidosis are commonly included in the differential diagnosis of mass lesions at lung and mediastinal sites. Once cancer is excluded on aspiration biopsy, further classification is essential for proper treatment. METHODS A search identified patients with histoplasmosis and sarcoidosis for whom the diagnosis was made by clinicopathologic correlation. Cases were reviewed for various cytologic parameters along with patient demographic, clinical, and laboratory data. RESULTS Fifty‐eight cases of histoplasmosis and 44 cases of sarcoidosis were reviewed. Thirty‐seven of 58 (64%) Histoplasma cases exhibited abundant, bland necrosis, and 76% of cases contained <2 angular and ragged granulomas per slide. Yeasts were identified in 36 of 37 (97%) specimens with necrosis and in 44 of 58 (76%) cases overall. These cases had an acute (14%) and/or chronic (67%) inflammatory component and uncommonly had a giant cell infiltrate (12%). Sarcoid granulomas were round with crisp, sharp borders: 80% of these granulomas contained >3 granulomas per slide, and 32% contained >10 granulomas per slide. All sarcoid granulomas had a chronic inflammatory background without acute inflammatory cells, and 50% contained giant cell infiltrates. CONCLUSIONS Differentiation between histoplasmosis and sarcoidosis is possible in the majority of cases. Histoplasmosis usually exhibits few angular, ragged granulomas (<2 granulomas per slide) in a background of bland necrosis. Yeasts are identified on special stains performed in aspirate smears. Sarcoidosis typically contains many more granulomas (often >10 per slide) than histoplasmosis and has a rounded morphology with crisp and sharp borders. Typically, there is no necrosis or acute inflammation, and giant cell infiltrates are frequent. Cancer (Cancer Cytopathol) 2015;123:51–8. © 2014 American Cancer Society.